Roles of parental stress and children’s emotional skills on behavioral responses: evidence from NSCH parent reports - Fa Zhang; Chin-Chih Chen; Yuyan Xia; Yaoying Xu; Jamie Cage (Frontiers in Psychology)
IntroductionEarly self-regulation is a crucial predictor of how well preschoolers respond to challenging, frustrating, and distracting situations. Examining the mediating role of contextual and individual factors provides insight into how external influences and personal characteristics shape children’s ability to navigate these challenges. This study aims to investigate whether specific contextual (e.g., parental stress) and individual (e.g., emotional skills) factors mediate the relationship between preschoolers’ self-regulation and their behavioral responses to transitions, frustration, and distraction.MethodsWe utilized data from the 2021 National Survey of Children’s Health, which includes a nationally representative sample of children aged 3–5 in the U.S. (N = 11,554). Structural equation modeling was employed to examine the mediating effects of parental stress (contextual factor) and emotional skills (individual factor) on the association between preschoolers’ self-regulation and their behavioral responsiveness.ResultsThe analysis revealed that higher levels of self-regulation were associated with more positive emotional skills, lower parental stress, and improved behavioral responsiveness in children. Among the mediators, parental stress significantly mediated the relationship between preschoolers’ self-regulation and behavioral responsiveness, while emotional skills did not show a significant mediating effect.DiscussionThese findings suggest that contextual factors, particularly parental stress, play a more substantial mediating role than individual emotional skills in shaping the relationship between self-regulation and behavioral responses in preschoolers. This highlights the importance of addressing parenting-related stress in intervention programs aimed at supporting children’s behavioral development.